2010
DOI: 10.1111/j.1365-2818.2009.03273.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical phenol extraction of intermetallic particles from casting AlSi5Cu1Mg alloy

Abstract: SummaryThis paper presents a chemical extraction technique for determination of intermetallic phases formed in the casting AlSi5Cu1Mg aluminium alloy. Commercial aluminium alloys contain a wide range of intermetallic particles that are formed during casting, homogenization and thermomechanical processing. During solidification, particles of intermetallics are dispersed in interdendritic spaces as fine primary phases. Coarse intermetallic compounds that are formed in this aluminium alloy are characterized by un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…It can be concluded that, with the adding of the content of La, there is a significant difference in the grain refinement effect. The microstructure of as-cast AlSi5Cu1Mg alloy consists of a wide range of intermetallic phases such as α-Al, Al4Fe, γ-Al3FeSi, α-Al8Fe2Si, β-Al5FeSi and Al12FeMnSi phase [25]. The matrix α-Al of as-cast AlSi5Cu1Mg alloy exhibits coarse dendrites and irregular shapes of clutter (Figure 2a).…”
Section: Microstructure and Microhardnessmentioning
confidence: 99%
“…It can be concluded that, with the adding of the content of La, there is a significant difference in the grain refinement effect. The microstructure of as-cast AlSi5Cu1Mg alloy consists of a wide range of intermetallic phases such as α-Al, Al4Fe, γ-Al3FeSi, α-Al8Fe2Si, β-Al5FeSi and Al12FeMnSi phase [25]. The matrix α-Al of as-cast AlSi5Cu1Mg alloy exhibits coarse dendrites and irregular shapes of clutter (Figure 2a).…”
Section: Microstructure and Microhardnessmentioning
confidence: 99%
“…69 The addition of 1% Cu to Al-Si alloys increased the transition load for mild to severe wear by three to four times that of the original alloys by increasing the stability and strength of the surface layer. 70 Hanafee 71 reported on the positive effect of magnesium, which precipitates out as a finely dispersed b-Mg 2 Si under controlled precipitation, 72 to the surface hardness of heat treated Al Alloys. However, these IMPs also impact the corrosion resistance of the alloys through the creation of galvanic cells with the surrounding a-Al matrix in the presence of an aqueous solution.…”
Section: Tribology Corrosion and Environmentsmentioning
confidence: 99%
“…The 6xxx-series aluminium alloys contains magnesium and silicon as major alloying elements [6][7][8][9][10][11][12]. These multiphase alloys belong to the group of commercial aluminum alloys, in which relative volume; chemical composition and morphology of structural constituents exert significant influence on their useful properties [1,[6][7][8][9][10][11]. Al-Mg-Si alloys that combine good strength, extrudability, favorable corrosion resistance with low cost have recently been used for automotive body sheet panel for weight saving, furniture, architectural facing and structures and transport vehicle frames.…”
Section: Introductionmentioning
confidence: 99%